2017
DOI: 10.18240/ijo.2017.05.09
|View full text |Cite
|
Sign up to set email alerts
|

Iontophoresis-assisted corneal crosslinking using 0.1% riboflavin for progressive keratoconus

Abstract: I-CXL using 0.1% riboflavin halts keratoconus progression within 24mo, resulting in a significant improvement in visual and topographic parameters. Moreover, the depth of the demarcation line is similar to that previously reported in standard epithelium-off CXL procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…A small current of 1 mA is then applied for 5 min. Once adequate stromal soakage by riboflavin is confirmed through slit-lamp examination, the cornea is then irradiated with UV-A light ( 135 , 136 ).…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…A small current of 1 mA is then applied for 5 min. Once adequate stromal soakage by riboflavin is confirmed through slit-lamp examination, the cornea is then irradiated with UV-A light ( 135 , 136 ).…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…The first studies, designed as case series and nonrandomized small sample-sized clinical trials date back to 2014 and found decreases in average keratometry values and stabilization of uncorrected visual acuity (UCVA), corrected distance visual acuity (CDVA), corneal astigmatism, and endothelial cell density with 12 months [39-42] and 24 months [43] follow-up both in early and advanced keratoconus [20].…”
Section: Clinical Trials On Classic I-cxlmentioning
confidence: 99%
“…Other studies have shown inhibition of keratoconus progression within 24 months, resulting in a significant improvement in visual and topographic parameters. Riboflavin (0.1%) was used in iontophoresis-assisted corneal crosslinking [61]. Application of riboflavin in corneal stroma by iontophoresis for halting keratoconus progression was also suggested by Mencucci et al [59].…”
Section: Vitaminsmentioning
confidence: 99%